2014
DOI: 10.5367/te.2014.0387
|View full text |Cite
|
Sign up to set email alerts
|

Shopping Tourism in Hungary during the Period of the Economic Crisis

Abstract: The study analyses the impacts brought about by the economic crisis starting in 2007 on Hungarian shopping tourism. Considering the long-term symbiotic relationship of the national retail trade and international inbound tourism, the crisis, that has affected each segment of the national economy, has also influenced both the characteristics of tourist shopping and the structure and volume of retail trade, with an indirect impact on the country's GDP. The study investigates the purchases of day trippers arriving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
1
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 31 publications
0
32
1
6
Order By: Relevance
“…Weaver and Oppermann (2000) observed that 30% of Australian tourism dollars were spent shopping, a number consistent with Snepenger, Murphy, O'Connell, and Gregg's (2003) estimate that one third of American tourism dollars derive from retail expenditures, ranking second only to accommodations as a source of tourism revenues (Turner & Reisinger, 2001). For many travelers, shopping is a relaxing and fulfilling source of recreation (Timothy & Butler, 1995), and there is a strong and consistent symbiotic relationship between shopping and tourism satisfaction (Michalkó, Rátz, Hinek, & Tömöri, 2014). Tourists thus enjoy shopping and a community's tourism economic success is likely dependent upon providing a strong retail presence (Lehto, Chen, & Silkes, 2014;Wu, Wall, & Pearce, 2014).…”
Section: Literature Reviewmentioning
confidence: 79%
“…Weaver and Oppermann (2000) observed that 30% of Australian tourism dollars were spent shopping, a number consistent with Snepenger, Murphy, O'Connell, and Gregg's (2003) estimate that one third of American tourism dollars derive from retail expenditures, ranking second only to accommodations as a source of tourism revenues (Turner & Reisinger, 2001). For many travelers, shopping is a relaxing and fulfilling source of recreation (Timothy & Butler, 1995), and there is a strong and consistent symbiotic relationship between shopping and tourism satisfaction (Michalkó, Rátz, Hinek, & Tömöri, 2014). Tourists thus enjoy shopping and a community's tourism economic success is likely dependent upon providing a strong retail presence (Lehto, Chen, & Silkes, 2014;Wu, Wall, & Pearce, 2014).…”
Section: Literature Reviewmentioning
confidence: 79%
“…Such obvious significance of the neighbouring markets for tourism in a particular country results from numerous factors. Undoubtedly, one of them is related to lower prices for some products or services (Michalkó, Rátz, Hinek and Tömöri, 2014). It is proved by T. T. Sikos and A. Kovács (2008) on the example of the Hungarian border shops during the devaluation of the forint.…”
Section: The Essence Of Tourist Traffic and Its Significance With Regmentioning
confidence: 97%
“…A vásárlással kapcsolatos tevékenységek, azaz a bevásárlóturizmus a 2000-es évek végéig erősen aszimmetrikus jelleggel bírt: a magyarok jóval nagyobb arányban utaztak bevásárlási szándékkal Ukrajnába (az utazások háromnegyedét ez tette ki), mint az ukránok Magyarországra (Kovály 2010). Ennek elsődleges oka a két ország termékei közötti árrés, valamint a forint-hrivnya árfolyam volt (Berghauer 2011), azonban e folyamatok alakulását általában komplex együtthatók eredményeiként kell vizsgálnunk (Michalkó et al 2014). Az általunk készített interjúk eredményeiből kiderül, hogy a magyarországiak bevá-sárlóturizmusa napjainkra veszített jelentőségéből, szemben az Ukrajnából érkező bevásárlóturisták számával.…”
Section: A Magyar-ukrán Határon áTívelő Kapcsolatok éS Mobilitásunclassified